Sporothrix brasiliensis and Feline Sporotrichosis in the Metropolitan Region of Rio de Janeiro, Brazil (1998–2018) - Jéssica Sepulveda Boechat; Manoel Marques Evangelista Oliveira; Isabella Dib Ferreira Gremião; Rodrigo Almeida-Paes; Ana Caroline de Sá Machado; Rosely Maria Zancopé-Oliveira; Raquel de Vasconcellos Carvalhaes Oliveira; Débora Salgado Morgado; Maria Lopes Corrêa; Anna Barreto Fernandes Figueiredo; Rodrigo Caldas Menezes; Sandro Antonio Pereira (Journal of Fungi, 2022)
Feline sporotrichosis is enzootic in different regions of Brazil, especially in Rio de Janeiro. This study compared the genotype profiles of Sporothrix sp. isolated from cats in Rio de Janeiro between 1998 and 2018 and evaluated their association with clinical and epidemiological characteristics. One hundred nineteen Sporothrix sp. isolates from a cohort of cats with sporotrichosis seen at INI/Fiocruz were included. Clinical and epidemiological data were obtained from the medical records of the animals. T3B PCR fingerprinting was used for molecular identification of the Sporothrix species. All isolates were characterized as Sporothrix brasiliensis, with the observation of low intraspecific variation in 31 isolates (31.3%). The interval between lesion onset and first medical visit at INI/Fiocruz, as well as treatment duration until clinical cure, was longer in cats from the first decade of the epizootic. In addition, the frequency of the variables “good general status” and “presence of lymphadenomegaly” was higher among cats whose strains did not exhibit intraspecific variation. So far, S. brasiliensis has been the only species identified in feline cases of sporotrichosis since the beginning of the epizootic in Rio de Janeiro at INI/Fiocruz.